Governance, risk, and compliance handbook for Oracle applications : written by industry experts with more than 30 years combined experience, this handbook covers all the major aspects of governance, risk, and compliance managent in your organization /: written by industry experts with more than 30 years combined experience, this handbook covers all the major aspects of governance, risk, and compliance managent in your organization. (©2012) - Unknown
No abstract available